Challenges associated with management of buruli ulcer/human immunodeficiency virus coinfection in a treatment center in Ghana: A case series study - Tuffour, J.; Owusu-Mireku, E.; Ruf, M.-T.; Aboagye, S.; Kpeli, G.; Akuoku, V.; Pereko, J.; Paintsil, A.; Bonney, K.; Ampofo, W.; Pluschke, G.; Yeboah-Manu, D. (American Journal of Tropical Medicine and Hygiene, 2015)
The synergy between Mycobacterium tuberculosis infection and human immunodeficiency virus (HIV)/ acquired immunodeficiency syndrome is well established but not so in Buruli ulcer (BU). We screened confirmed BU cases for HIV infection and followed seven BU/HIV-coinfected patients. Management of BU/HIV was based on the World Health Organization guidelines and patient condition. The HIV positivity among BU patients (8.2%; 11/134) was higher compared with that of general patients attending the facility (4.8%; 718/14,863; P = 0.07) and that of pregnant women alone (2.5%; 279/11,125; P = 0.001). All seven BU/HIV-coinfected cases enrolled in the study presented with very large (category III) lesions with four having multiple lesions compared with 54.5% of category III lesions among HIV-negative BU patients. During the recommended BU treatment with streptomycin and rifampicin (SR) all patients developed immune infiltrates including CD4 T cells in their lesions. However, one patient who received antiretroviral therapy (ART) 1 week after beginning SR treatment developed four additional lesions during antibiotic treatment, while two out of the four who did not receive ART died. Further evidence is required to ascertain the most appropriate time to commence ART in relation to SR treatment to minimize paradoxical reactions. © 2015 by The American Society of Tropical Medicine and Hygiene.
Keywords: Buruli Ulcer; Human Immunodeficiency Virus; Ghana